2007
DOI: 10.11646/zootaxa.1422.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of taipan (Elapidae: Oxyuranus) from central Australia

Abstract: Snakes in the Australo-Papuan elapid genus Oxyuranus are considered to be the most venomous species in the world. A recent expedition to the central ranges of Western Australia discovered a third species, which is described here from the only known specimen. Molecular genetic analyses using mitochondrial nucleotide sequences places the new species as the sister lineage of the two described Oxyuranus species, with all three species united by a long branch that also separates them from the nearest of the brown s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…often result in severe neurotoxic envenoming which may be fatal in the absence of prompt antivenom treatment [3,4]. There are three species of taipans: (a) O. scutellatus, with populations in northern Australia, southern Papua New Guinea and southern Indonesian Papua [1,5,6]; (b) Oxyuranus microlepidotus, the inland taipan, which occurs in south-western Queensland and north-eastern to centralnorthern South Australia [7]; and (c) Oxyuranus temporalis, known from a handful of specimens collected in the southeastern deserts of Western Australia [7]. O. scutellatus occurs in a wide variety of habitats including sugarcane fields and woodlands in the eastern and north coast of Australia and in savannah regions of southern New Guinea [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…often result in severe neurotoxic envenoming which may be fatal in the absence of prompt antivenom treatment [3,4]. There are three species of taipans: (a) O. scutellatus, with populations in northern Australia, southern Papua New Guinea and southern Indonesian Papua [1,5,6]; (b) Oxyuranus microlepidotus, the inland taipan, which occurs in south-western Queensland and north-eastern to centralnorthern South Australia [7]; and (c) Oxyuranus temporalis, known from a handful of specimens collected in the southeastern deserts of Western Australia [7]. O. scutellatus occurs in a wide variety of habitats including sugarcane fields and woodlands in the eastern and north coast of Australia and in savannah regions of southern New Guinea [5].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic differences between the New Guinean and Australian populations of the taipan had prompted their classification as separate subspecies, Oxyuranus scutellatus canni and Oxyuranus s. scutellatus, respectively [8]. However, recent evidence from mitochondrial DNA analysis revealed high similarities between these populations, demonstrating very recent genetic exchange among them, thus questioning their subspecific status [6,7]. Hence, further studies are required to assess the intraspecies variation between these populations.…”
Section: Introductionmentioning
confidence: 99%
“…For many years the Papuan taipan has been regarded as a separate subspecies ( Oxyuranus s. canni ) to Australian populations ( Oxyuranus s. scutellatus ). However, recent taxonomic and biogeographical studies have shown that, despite some perceived morphological differences, molecular genetic analysis reveals no significant differentiation between the two populations [6], [7]. On this basis, O. scutellatus is now considered a single species with both Australian and New Guinean populations.…”
Section: Introductionmentioning
confidence: 99%
“…Such species discoveries can be due to a number of reasons; amphibians and reptiles are generally smaller, less mobile and thus less conspicuous than their more mobile and conspicuous counterparts such as birds and mammals. In Australia, many species have adapted to inhabit remote, arid regions of the continent that are often inhospitable to mammals and birds and rarely visited by people (Doughty et al 2007a;Doughty et al 2007b). Cryptic behaviour and/or highly conserved morphology between related species can also make it difficult to recognise new species (Oliver et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%